SiRNA‐Mediated Down‐Regulation of CLIC4 Gene Inhibits Cell Proliferation and Accelerates Cell Apoptosis of Mouse Liver Cancer Hca‐F and Hca‐P Cells. Issue 1 (31st July 2017) - Yu, Qiu‐Yun; Zhou, Xin‐Feng; Xia, Qing; Shen, Jia; Yan, Jia; Zhu, Jiu‐Ting; Li, Xiang; Shu, Ming
ABSTRACT: This study explored the effects involved in silencing CLIC4 on apoptosis and proliferation of mouse liver cancer Hca‐F and Hca‐P cells. A CLIC4‐target small interfering RNA (siRNA) was designed to compound into two individual complementary oligonucleotide chains. A process of annealing and connection to a pSilencer vector was followed by transfection with Hca‐F and Hca‐P cells. Quantitative real‐time polymerase chain reaction and Western blotting techniques were used to determine CLIC4 mRNA and protein expressions. CCK8 assay and flow cytometry were employed for analysis of the survival and apoptosis rate as well as the cell cycle in an octreotide‐induced apoptosis model. Expressions of caspase 3, caspase 9, and cleaved PARP were measured using Western blotting. The CLIC4 mRNA and protein expressions in Hca‐F and Hca‐P cells transfected by pSilencer‐CLIC4 siRNA plasmid in the blank group displayed remarkably decreased levels of expression, when compared with both the control and negative control (NC) groups. Decreased survival rates and cleaved PARP expression, increased cell apoptosis rate, expressions of caspase 3 and caspase 9 in Hca‐F and Hca‐P cells were detected in groups that had been cultured in a medium containing octreotide. The pSilencer‐CLIC4 siRNA‐2 group when compared with the control and NC groups exhibited decreased survival rates, cleaved PARP expression, increased cell apoptosis rates, and increased expressions of caspase 3 and caspase 9 of Hca‐F and Hca‐P cells. The results demonstrated that siRNA‐induced down‐regulation of CLIC4 could proliferation, while in turn promoting apoptosis of mouse liver cancer Hca‐F and Hca‐P cells. J. Cell. Biochem. 119: 659–668, 2018. © 2017 Wiley Periodicals, Inc. Abstract : These results demonstrate that down‐regulating CLIC4 inhibit the proliferation and promotes the apoptosis of mouse liver cancer Hca‐F cell.